2018
DOI: 10.1080/15476286.2018.1517011
|View full text |Cite
|
Sign up to set email alerts
|

DDX39B promotes translation through regulation of pre-ribosomal RNA levels

Abstract: DDX39B, a DExD RNA helicase, is known to be involved in various cellular processes such as mRNA export, splicing and translation. Previous studies showed that the overexpression of DDX39B promotes the global translation but inhibits the mRNA export in a dominant negative manner. This presents a conundrum as to how DDX39B overexpression would increase the global translation if it inhibits the nuclear export of mRNAs. We resolve this by showing that DDX39B affects the levels of pre-ribosomal RNA by regulating it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…We found that the RNA binding motif protein (RBM) family members (RBM5/6/25/33/39), SRRM1/2 and SRSF5/6/11, were in the central genes and played a role in the splicing and processing of mRNA. Moreover, two of the top 3 genes of intramodular connectivity (DDX39B and LUC7L) also serve important roles in alternative RNA splicing (Figure A and Table ) …”
Section: Resultsmentioning
confidence: 99%
“…We found that the RNA binding motif protein (RBM) family members (RBM5/6/25/33/39), SRRM1/2 and SRSF5/6/11, were in the central genes and played a role in the splicing and processing of mRNA. Moreover, two of the top 3 genes of intramodular connectivity (DDX39B and LUC7L) also serve important roles in alternative RNA splicing (Figure A and Table ) …”
Section: Resultsmentioning
confidence: 99%
“…Awasthi et al revealed that DDX39B was important for maintaining the normal levels of pre-ribosomal RNA by controlling its stability and synthesis. In addition, DDX39B was frequently upregulated in many cancer types and promoted the proliferative capacity of cells [21]. Activation of androgen receptor (AR) splice variants, especially AR-V7, are associated with unfavorable clinical outcome of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…JMJD6 is a histone demethylase that can demethylate histone H3 ( 43 ) and regulates nuclear factor κB (NF-κB) ( 44 ), both of which have been implicated in cocaine-associated plasticity ( 45 , 46 ). DDX39B is an RNA helicase that promotes translation through regulation of preribosomal RNA levels ( 47 ). mRNA expression of these genes matched INO80 binding patterns, and viral manipulation of INO80 affected these targets.…”
Section: Discussionmentioning
confidence: 99%